Genetic structure of Rattus rattus populations in an endemic plague focus in Madagascar: Implications for rodent surveillance and management - Mamionah N. J. Parany; Anne Loiseau; Philippe Gauthier; Soanandrasana Rahelinirina; Gauthier Dobigny; Olivier Gorgé; Eric Valade; Minoarisoa Rajerison; Beza Ramasindrazana; Carine Brouat (PLoS ONE, 2026)
Background Plague remains a major public health concern in Madagascar. In the Central Highlands, where the disease is still endemic, the black rat ( Rattus rattus ) is the main reservoir of the causative agent Yersinia pestis . Understanding its population dynamics and structure is therefore crucial to inform control strategies, as dispersal may greatly limit the effectiveness of local interventions during outbreaks. In this context, our study investigates the genetic structure of R. rattus populations at a fine geographical scale and across two different years. Methodology/Principal findings Sampling was conducted in six villages of the Azobenzene district, both inside houses and in habitat outside villages. A total of 480 individuals, captured in March – May 2019 and 2020, were genotyped at 18 microsatellite loci. Our results showed that genetic diversity levels were relatively similar among villages and years. However, subpopulations living outside villages displayed significantly higher genetic diversity and lower genetic differentiation levels than those from inside houses, indicating larger effective population sizes outside villages in the cultivated habitats. These findings suggest more restricted movement among rat subpopulations from the houses, and greater connectivity among subpopulations living outside villages. However, overall genetic differentiation was rather low, suggesting extensive dispersal of rats at the scale of the district, facilitating rapid recolonization after local control efforts. Conclusion Because of the recolonization problem, an integrated approach combining flea control inside houses together with measures to reduce human-rodent contact would thus appear more appropriate than rodent control only to limit plague transmission.